2020
DOI: 10.48084/etasr.3378
|View full text |Cite
|
Sign up to set email alerts
|

Use of Marble Powder and Tile Powder as Cementitious Materials in Concrete

Abstract: The use of agricultural and industrial waste products as raw materials in the construction industry is investigated extensively. These products are inexpensive and help in environmental sustainability, as environmental pollution is thus reduced. This study focused in investigating the properties of fresh, physical and hardened concrete blended with marble (MP) and tile powder (TP) of several proportions, such as 0%, 5% (2.5%MP + 2.5%TP), 10% (5%MP + 5%TP), 15% (7.5%MP + 7.5%TP), and 20% (10%MP + 10%TP) by weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…is decrement in the density of concrete with the addition of BCM is due to the specific gravity of cement being higher than that of metakaolin and GGBFS. is observation is similar to that of [5], where the density of concrete decreases with increasing marble and tile powder content in concrete after 28 days. Also, Raza et al [43] reported that the concrete density decreases as the amount of wood waste ash increases in concrete after 28 days.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…is decrement in the density of concrete with the addition of BCM is due to the specific gravity of cement being higher than that of metakaolin and GGBFS. is observation is similar to that of [5], where the density of concrete decreases with increasing marble and tile powder content in concrete after 28 days. Also, Raza et al [43] reported that the concrete density decreases as the amount of wood waste ash increases in concrete after 28 days.…”
Section: Resultssupporting
confidence: 84%
“…Bheel et al [42] indicated that the compressive strength was improved while using 10% of BCM in concrete after 28 days. Similarly, Bheel et al [5] described that the use of marble and tile powder up to 10% as cementitious material caused an increase in strength after 28 days.…”
Section: Compressive Strengthmentioning
confidence: 92%
See 1 more Smart Citation
“…The usage of partially replacement cementitious materials (RCMs) with cement which decreasing the pollution impact and saving environment from the factories, mills and the industries. RCMs materials are Palm-Kennel Shell (PKS), Saw Dust Ash (SDA), Corn Cob Ash (CCA), Millet Husk Ash (MHA), Rise Husk Ash (RHA), Sugarcane Bagasse Ash (SCBA), Groundnut Shell Ash (GSA), etc [14], [15], [16], [17]. These replacements can be improved the workability, durability, early and long term strength and economy based in the blended cement concrete [18].…”
Section: Introductionmentioning
confidence: 99%
“…The hardening of concrete is attained through hydration which is an exothermic reaction between cement and water. The addition of water to concrete during mixing enables hydration to take place while the excess quantity forms a slurry with the cement which coats the aggregates in the mix, lubricating them and allowing easy movement during compaction [3]. The first stage of hydration that leads to stiffening is caused by the reaction between water and a chemical constituent of cement called tricalcium silicate (C 3 S) [4].…”
Section: Introductionmentioning
confidence: 99%